2022
DOI: 10.1155/2022/3580711
|View full text |Cite|
|
Sign up to set email alerts
|

Certain Structure of Lagrange’s Theorem with the Application of Interval-Valued Intuitionistic Fuzzy Subgroups

Abstract: This paper presents the concept of an interval-valued intuitionistic fuzzy subgroup defined on interval-valued intuitionistic fuzzy sets. We study some of the fundamental algebraic properties of interval-valued intuitionistic fuzzy cosets and interval-valued intuitionistic fuzzy normal subgroup of a given group. This idea is used to describe the interval-valued intuitionistic fuzzy order and index of interval-valued intuitionistic fuzzy subgroup. We have created numerous algebraic properties of interval-valued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Structure preserving LIFSG-3 maps are also discussed, and it is observed that they can be derived by extending group homomorphism. In the future, the notion foundations laid in this article can be used to find the Abelian subgroups of finite p -groups [ 34 ], verify Lagrange's theorem [ 35 , 36 ], compute annihilator [ 37 ], aggregation [ 38 ], and fundamental isomorphism theorems [ 39 ] for lattice-valued intuitionistic fuzzy subgroups type-3. There are several generalizations of fuzzy sets [ 40 42 ] where lattice-valued algebraic structures can be defined by replacing [0,1] with a suitable lattice L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure preserving LIFSG-3 maps are also discussed, and it is observed that they can be derived by extending group homomorphism. In the future, the notion foundations laid in this article can be used to find the Abelian subgroups of finite p -groups [ 34 ], verify Lagrange's theorem [ 35 , 36 ], compute annihilator [ 37 ], aggregation [ 38 ], and fundamental isomorphism theorems [ 39 ] for lattice-valued intuitionistic fuzzy subgroups type-3. There are several generalizations of fuzzy sets [ 40 42 ] where lattice-valued algebraic structures can be defined by replacing [0,1] with a suitable lattice L .…”
Section: Discussionmentioning
confidence: 99%
“…Lattice-valued intuitionistic fuzzy normal subgroups type-3 and latticevalued intuitionistic fuzzy factor subgroups type-3 of G are governed by normal subgroups and factor groups of G. Structure preserving LIFSG-3 maps are also discussed, and it is observed that they can be derived by extending group homomorphism. In the future, the notion foundations laid in this article can be used to find the Abelian subgroups of finite p-groups [34], verify Lagrange's theorem [35,36], compute annihilator [37], aggregation [38], and fundamental isomorphism theorems [39] for lattice-valued intuitionistic fuzzy subgroups type-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This section is devoted to present three definitions and lemmas that will be used in the paper [5]. Definition 1 (subgroup).…”
Section: Definitions and Lemmasmentioning
confidence: 99%
“…In Ref. [ 43 ], Kattan et al proved the interval-valued intuitionistic fuzzy version of Lagrange's theorem.…”
Section: Introductionmentioning
confidence: 99%